Research Opportunities in Supply Chain Transparency - Sodhi, ManMohan S.; Tang, Christopher S. (Production and Operations Management, 2019)
More firms than ever before are disclosing the provenance of their products, results of product testing, and suppliers’ compliance with labor‐practice norms in their annual reports, sustainability reports, and press releases, besides making such information available on third‐party websites. However, collecting and disclosing such information is not only costly but also does not provide clear benefits. While the terminology is not yet standard in the literature, this study distinguishes supply chain transparency from visibility. Here, visibility refers to managers’ efforts to learn more about operations upstream in their supply chains. In contrast, by transparency, we mean a company disclosing information to consumers, investors, and other stakeholders about compliance with consumer‐expected norms in its supply chain operations and products. To motivate further research on supply chain transparency, we first report recent examples of companies providing supply chain transparency. Then we present potential benefits of supply chain visibility and supply chain transparency, respectively, for the company. Finally, we propose topics for research on supply chain transparency arranged by stakeholder.